A construção do conhecimento sobre a água por meio de uma sequência didática que emprega a estratégia de experimentação - Lovato, Luciana Bonato (My University, 2018)
Water is an indispensable natural resource for survival. Its preservation is linked to human daily activities. Making the students aware about the necessity of its preservation through conscious use is an alternative to guarantee drinking water for the future generations. In this context, this research had as objective to elaborate, implement and analyze a didactic sequence on the theme "Water", contemplating different strategies in the teaching of Sciences for the sixth year of Elementary School, establishing a continuous evaluation process that would break the relations of power built in the everyday classroom and make teachers and students partners in evaluation and learning. There were used several didactic strategies to develop the activities, such as experiments, questioning, observation, group works, videos, synthesis construction, among others, in an attempt to meet the individualities of each student. The didactic sequence was constructed during 2015 with an "ideal class", but it needed adjustments to work with the test group in 2016, since the latter was quite heterogeneous and more difficult to work than the first. As a result, it was observed that the students showed great interest in participating in the proposed activities, both in the pilot group and in the test group. In addition, in both, it was verified that there was construction of knowledge. As a result, it was observed that the students showed great interest in participating in the proposed activities, both in the pilot group and in the test group. In addition, in both, it was verified that there was construction of knowledge. It was concluded that in proposing different strategies for the construction of knowledge on the subject, it was possible for the students to have a global view of the fundamental concepts on water, favoring the relations between scientific and everyday knowledge, as well as allowing a re-signification of values aiming at conscious consumption and the preservation of this natural resource essential for life. The final product of this study is a didactic guide of Sciences for the Elementary School, which describes procedures for a differentiated approach of the contents related to the theme water.
A água é um recurso natural imprescindível para a sobrevivência. Sua preservação está atrelada à atividade cotidiana do homem. Sensibilizar os estudantes sobre a necessidade da sua preservação através do uso consciente é uma alternativa para garantir água potável para as gerações futuras. Neste contexto, esta pesquisa teve como objetivo elaborar, implementar e analisar uma sequência didática sobre o tema “Água”, contemplando diferentes estratégias no ensino de Ciências para o 6º ano do Ensino Fundamental, estabelecendo um processo avaliativo contínuo, que rompesse as relações de poder construídas no cotidiano da sala de aula e tornasse professores e estudantes parceiros na avaliação e aprendizagem. Foram utilizadas diferentes estratégias didáticas para desenvolver as atividades, tais como experimentos, problematização, observação, trabalhos em grupo, vídeos, construção de sínteses, entre outras, na tentativa de se atender às individualidades de cada estudante. A sequência didática foi construída ao longo de 2015 com uma “turma ideal”, mas necessitou de ajustes para funcionar com a turma de testagem em 2016, uma vez que esta ultima era bastante heterogênea e mais difícil de trabalhar do que a primeira. Como resultados, observou-se que os estudantes manifestaram grande interesse em participar das atividades propostas, tanto na turma piloto, quanto na turma de testagem. Além disso, em ambas verificou-se que houve construção de conhecimentos. Concluiu-se que ao propor diferentes estratégias para a construção de conhecimento sobre o tema possibilitou aos estudantes uma visão global dos conceitos fundamentais sobre água, favorecendo as relações entre o saber científico e o cotidiano, além de permitir uma ressignificação de valores visando o consumo consciente e a preservação deste recurso natural essencial à vida. O produto final deste estudo é um guia didático de Ciências para o Ensino Fundamental, que descreve procedimentos para uma abordagem diferenciada dos conteúdos referentes ao tema água.
Keywords: Água - Consumo; Construtivismo (Educação); Water consumption; Constructivism (Education)